IMMUNOHISTOCHEMICAL DETECTION OF KI67 AND HER2 IN CERVICAL TUMORS AMONG SUDANESE WOMEN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This is a descriptive study aimed to detect the expression of Ki67 and Her2 tumor markers in cervical tumors. Forty-five formalin fixed paraffin blocks were randomly selected from women samples previously diagnosed as cervical tumors (Thirty-five samples were malignant tumors and ten samples were benign tumors). The paraffin blocks were cut by rotary microtome and stained by immunohistochemical method for detection of Ki67 and Her2. The data obtained was analyzed using SPSS program. The  malignant  tumors  included  29  (83%)  samples  were  squamous  cell  carcinoma  and  remaining  6  (17%)  samples  were adenocarcinoma.The patient age ranged from 27 to 85 years with mean age of 57 years. From the samples 14 (31%) samples were Ki67 positive (all of them were malignant) and 31 (69%) samples were Ki67 negative (P value 0.05).  This study concluded that the expression of Ki67 and Her2 is associated with malignant tumors of the cervix, also concluded that there was significant different between Ki67 and histopathological grade while there were no significant different between Her2 expression and the histopathological grade.